Micropropagation of Three Endemic Begonias Using Various Hormones Concentration and Culture Media Application - Ismaini, Lily; Lailaty, Intani Quarta; Efendi, Muhammad (UIN Sunan Gunung Djati Bandung, 2021)
Three species of Begonias endemic to Java and Sumatra, namely Begonia leuserensis, Begonia atricha and Begonia scottii, were conserved in Cibodas Botanic Gardens as sources of germplasm for ornamental plant and/or medicines. However, the information on efficient hormones concentration and their culture media application through an in vitro propagation effort is still limited. Therefore, this study aimed to explain the growth response of three species of Begonias using various hormones concentrations and culture media through in vitro propagation. The culture media using Murashige & Skoog (MS) media that combinedwith 6-Benzyladenine (BA) dan Thidiazuron (TDZ) hormones in different concentrations i.e. 0.5 mg/L, 1 mg/L, 2 mg/L, and 3 mg/L. Observation parameter included shoot number, plantlets height, and leaves number. The data were analyzed using analysis of variance (ANOVA) with the F test at a 5% significance level. The results showed that three species of Begonias were observed to have different growth responses in the combination of MS+BA and MS+TDZ media. The combination of MS+TDZ media produces more shoots number, while the combination of MS+BA media influenced higher in leaves number. A concentration of 0.5 mg/L of hormone showed a good regeneration, therefore were recommended for in vitro propagation of Begonia species.